Developing a new device for continuously recording, in vivo, the excretion rate of sweat (perspiration) in humans. Issue 4 (13th February 2019) - Caberlotto, Elisa; Guillou, Carole; Colomb, Loic; Barla, Charlie; Salah, Samir; Vicic, Marco; Revol‐Cavalier, Frederic; Rat, Venceslass; Filipe, Sabine; Flament, Frederic
Abstract : Background: Some methodologies used for evaluating sweat production and antiperspirants are of a stationary aspect, that is, most often performed under warm (38°C) but resting conditions in a rather short period of time. The aim is to develop an electronic sensor apt at continuously recording sweat excretion, in vivo, during physical exercises, exposure to differently heated environments, or any other stimuli that may provoke sweat excretion. Material and Methods: A sensor (20 cm 2 ) is wrapped under a double‐layered textile pad. Fixed onto the armpits, these two arrays of electrodes are connected to electronic system through an analog multiplexer. A microcontroller is used to permanently record changes in the conductance between two electrodes during exposure of subjects to different sweat‐inducing conditions or to assess the efficacy of applied aluminum hydrochloride (ACH)‐based roll‐ons at two concentrations (5% and 15%). Results: In vitro calibration, using a NaCl 0.5% solution, allows changes in mV to be related with progressively increased volumes. In vivo, results show that casual physical exercise leads to sweat excretions much higher than in warm environment (37 or 45°C). Only, an exposure to a 50°C environment induced comparable sweat excretion. In this condition, sweat excretions were found similar in both armpits and both genders. Decreased sweat excretions were recorded following applications of ACH, with a dose effect. Conclusion: Developing phases of this new approach indicate that usual method or guidelines used to determine sweat excretions in vivo do not reflect true energy expenditure processes. As a consequence, they probably over‐estimate the efficacy of antiperspirant agents or formulae.